Paliperidone Induced Hypoglycemia by Increasing Insulin Secretion - Tsubasa Omi; Keisen Riku; Motoyuki Fukumoto; Koji Kanai; Yumi Omura; Hiromune Takada; Hidenori Matunaga (Case Reports in Psychiatry)
We report the case of a 41-year-old woman with schizophrenia who developed persistent hypoglycemia following paliperidone administration. After discontinuing paliperidone, the hypoglycemia resolved, but symptoms of diabetes emerged. Therefore, it appears that the hypoglycemia induced by paliperidone may mask symptoms of diabetes. Paliperidone may induce hypoglycemia by increasing insulin secretion. This report could help elucidate the relationship between atypical antipsychotics and glucose metabolism.